To solve for y, we need to combine like terms on the left side of the equation.
First, we have 6y and -9y. This means we have 6y - 9y, which simplifies to -3y.
So now our equation is: -3y + 6 = -12.
Next, we can subtract 6 from both sides to isolate the variable y.
-3y + 6 - 6 = -12 - 6
This simplifies to:
-3y = -18
To solve for y, we can divide both sides of the equation by -3.
(-3y) / -3 = (-18) / -3
Simplifying further:
y = 6
Therefore, the solution to the equation is y = 6.
Solve for y.
6y−9y+6=−12
1 answer